(untitled) (SMC Journal Shadananda Multiple Campus, 2025)
Adolescents in Nepal face challenges such as early marriage, high adolescent pregnancy rates, low contraceptive use, and limited access to reproductive health services, particularly in rural areas. Addressing socio-cultural, educational, and economic barriers is crucial for improving reproductive health outcomes. This study explores adolescents’ awareness, access, and use of safe abortion services in Sankhuwasabha, analyzing socio-cultural and economic influences on reproductive health behaviors. It also evaluates the effectiveness of youth-friendly Sexual and Reproductive Health (SRH) services. The research aims to bridge critical gaps in adolescent reproductive health by examining barriers to safe abortion services. The findings will help inform policies to enhance youth-friendly SRH programs and contribute to improved maternal health outcomes through increased awareness and intervention strategies. Using a mixed-methods approach, the study combines qualitative (interviews, focus group discussions) and quantitative (structured surveys) methods. It applies the socio-ecological model, reproductive justice theory, and the Health Belief Model to assess influences at individual, community, and policy levels. The study reveals low awareness of abortion legality (56%), high early marriage and childbearing rates, low contraceptive use (14%), and significant socio-cultural barriers. While Sankhuwasabha has 18 health facilities providing safe abortion services, access remains limited in rural areas due to affordability and awareness issues. Comprehensive health education, youth-friendly SRH services, and multi-sectoral interventions are essential to improving reproductive health outcomes, increasing awareness, reducing stigma, and ensuring better accessibility for adolescents.